Testing the role of urban development in the conventional Environmental Kuznets Curve: evidence from Turkey - Katircioglu, Setareh; Katircioglu, Salih (Routledge Journals, Taylor & Francis Ltd, 2018)
We tested the role of urbanization in the conventional Environmental Kuznets Curve (EKC) of Turkey's developing economy and rapid urbanization. The effects of an increase in carbon dioxide emissions were due to the usage of fuel oil and other traditional energy consumption patterns related to urban development. Based on our findings, we suggest that the EKC of Turkey is not an inverted U-shape. Thus, adapting of alternative and clean energy systems is necessary and unavoidable in Turkey, and Turkish authorities should consider renewable and alternative uses of energy to sustain a stable EKC.
Keywords: Environmental Kuznets Curve; energy; carbon emissions; urbanization; C22; C51; O13; O18